2016
DOI: 10.5588/ijtld.15.1019
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of levels of fractional exhaled nitric oxide in patients with pulmonary tuberculosis

Abstract: FeNO levels do not appear to be affected in PTB patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
1
5
0
1
Order By: Relevance
“…A study in Taiwan had reported increased FeNO levels in active TB patients, assuming increased lung macrophage activity and up-regulation of iNOS [10]. They found a median FeNO value of 15 ppb in healthy control subjects, parallel to values reported in Vietnamese construction workers (15 ppb) and healthy controls in the Indonesian study (16.6 ppb), but higher than that in controls in the Taiwanese study (6.5 ± 0.9 ppb) and lower than mean values observed in Korean controls (27.06 ± 10.8 ppb) and Yhi study 2016 [21] [22]. The FeNO level unevenness in healthy controls was furthermore demonstrated in the Vietnam study: although FeNO was greater in TB participants compared with a subgroup of healthy hospital workers, they were not significantly different on comparison with healthy construction workers [23].…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…A study in Taiwan had reported increased FeNO levels in active TB patients, assuming increased lung macrophage activity and up-regulation of iNOS [10]. They found a median FeNO value of 15 ppb in healthy control subjects, parallel to values reported in Vietnamese construction workers (15 ppb) and healthy controls in the Indonesian study (16.6 ppb), but higher than that in controls in the Taiwanese study (6.5 ± 0.9 ppb) and lower than mean values observed in Korean controls (27.06 ± 10.8 ppb) and Yhi study 2016 [21] [22]. The FeNO level unevenness in healthy controls was furthermore demonstrated in the Vietnam study: although FeNO was greater in TB participants compared with a subgroup of healthy hospital workers, they were not significantly different on comparison with healthy construction workers [23].…”
Section: Discussionsupporting
confidence: 68%
“…Elevated exhaled NO and NOS2 expression in alveolar macrophages is found in patients with active tuberculosis and is decreased with anti-tuberculous therapy [10]. A longitudinal study in Korean TB participants also demonstrated no significant change following 8 weeks of treatment [21]. Likewise, only a very small variation was observed in mean FeNO levels at treatment completion in the Indonesian study, 10.7 -15.1 ppb, which falls within the precision range for the portable NO analyzer device used (±5 ppb for values < 50 ppb).…”
Section: Discussionmentioning
confidence: 99%
“… 7 The recent longitudinal study in Korean TB participants also demonstrated no significant change following 8 weeks of treatment. 10 Similarly, only a very small change was observed in mean FeNO levels at treatment completion in the Indonesian study, 10.7–15.1 ppb, which falls within the accuracy range for the portable NO analyzer device used (±5 ppb for values < 50 ppb). Although, because of the limitation of our small sample size and low statistical power, we cannot exclude a small effect that might be observed in a larger study, this would not be clinically useful.…”
mentioning
confidence: 58%
“…We observed a median FeNO value of 15 ppb (IQR = 12–24) in healthy control subjects, similar to values reported in Vietnamese construction workers (15 ppb, IQR = 12–19) and healthy controls in the Indonesian study (16.6 ppb; 95% CI: 14.2–19.5), but higher than that in controls in the Taiwanese study (6.5 ± 0.9 ppb) and lower than mean values described in Korean controls (27.06 ± 10.8 ppb). 10 , 11 , 13 , 14 The FeNO level variability in healthy controls was furthermore demonstrated in the Vietnam study: although FeNO was greater in TB participants compared with a subgroup of healthy hospital workers, they were not significantly different when compared with healthy construction workers. 14 Participants with poor nutritional status were excluded from the Taiwanese study because of concerns regarding the effect on immunity.…”
mentioning
confidence: 86%
See 1 more Smart Citation